An Assessment of the Use of Rotary Wing Aircraft for Primary and Medical Emergency Care Service – Sabah State Experience - Nelbon Giloi; Lim Jac Fang; Mohammad Saffree bin Jeffree; Mohd Yusof Hj Ibrahim; Liew, Constance Sat Lin; Simson Gunsalam; Jennifer Lim Mei Ching (2020)
Introduction: Rotary wing aircraft (RWA) or the helicopter has been used in Primary Health Care and Medical Emergency Services in the state of Sabah since the seventies. The use of RWA has distinct advantages in terms of speed, ability to access remote areas and in the transportation of patients to tertiary care. Single engine RWA was used for the last forty years which has now been replaced with twin engine RWA. The objective of this study is to compare the different type of RWA which was used and the suitability of these machines for health services in Sabah. Methods: A detailed analysis and comparison of manufacturers’ specifications which include the performance, size, the number of power plant, passenger capacity, safety track record, aircraft manufacturer’ s support, maintenance and operational costs of different types of RWA available in Sabah taking into account current and future demands as well as functional requirements and the capability of the aircraft service providers were considered. Results: The choice of aircrafts depends on the type of service and its suitability. From the assessment, a single engine RWA would be adequate to support the current and future need in Sabah. Conclusion: Adequate technical knowledge in choosing the type of aircraft to provide an effective health service is vital. These also contribute to the cost effectiveness of the program and significantly determine efficiency of the service and the interest of the rural people with poor accessibility to health care.